I Didn’t Know that I Was Starving ‘Til I Tasted You: 18th Century Moravian Women’s Ecstatic Experience of Bridal Mysticism in Communion and Marital Sexuality - Wilkening, Ann-Catherine (Lumen et Vita, 2018)
Against recent moves to exoticize Moravian sexual practices, this project is an attempt to understand how sexuality and religion intersect and relate to each other in Moravian piety and theology. In the mid-18th century, Moravians practiced a deeply sensual and erotic form of bridal mysticism. Christ, the bridegroom and lover of the believer, became uniquely tangible to the Moravian in their experience of Holy Communion, as well as in sexual encounters with their spouse. This paper examines the realization of this union in the experience of Moravian women through their spiritual autobiographies (Lebenslauf) as well as the manuals for sexual intercourse in the 18th century Moravian Choir Instructions. During communion, women consumed the body of their eternal bridegroom with their own bodies, drawing close to Christ and nourished themselves through the ritualized breaking and bleeding of Jesus for their salvation. Moravians also understood marital sexual intercourse to be a blessed, liturgical act ordained by God and was it therefore an extremely ritualized act in which a husband represented Christ and a wife the Church. In encountering their husbands, Moravian women could encounter Christ. Sex was carefully directed to ensure its sacredness as well as the comfort of the couple.